1994
DOI: 10.1007/bf00571538
|View full text |Cite
|
Sign up to set email alerts
|

Local fibrinolysis for superior mesenteric artery thromboembolism

Abstract: A 66-year-old man with atrial fibrillation was referred soon after developing left lower limb and abdominal pain with rectal bleeding. An immediate flush aortogram showed embolic occlusion of the left distal superficial femoral artery and superior mesenteric artery (SMA), 3 cm from its ostium. Recombinant tissue plasminogen activator (rtPA) 40 mg was selectively instilled in the SMA in two boluses. Abdominal symptoms resolved within 48 h, and complete recanalization of the SMA was shown on angiography. Explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Thrombolytic therapy is most likely to be successful if treatment is started within 12 h of the onset of symptoms and if the thrombus partially occludes the SMA trunk or occludes a single SMA branch distal to the ileocolic artery. [62][63][64][65][66][67][68][69] It was reported that a routine transcatheter infusion of papaverine improved survival in highly selected patients with major emboli of the SMA, although the experience is limited. 50,70 …”
Section: Acute Mesenteric Arterial Embolus and Thrombusmentioning
confidence: 99%
“…Thrombolytic therapy is most likely to be successful if treatment is started within 12 h of the onset of symptoms and if the thrombus partially occludes the SMA trunk or occludes a single SMA branch distal to the ileocolic artery. [62][63][64][65][66][67][68][69] It was reported that a routine transcatheter infusion of papaverine improved survival in highly selected patients with major emboli of the SMA, although the experience is limited. 50,70 …”
Section: Acute Mesenteric Arterial Embolus and Thrombusmentioning
confidence: 99%
“…In the setting of a hemodynamically stable patient, with no signs of peritonitis, conservative medical [63][64][65][66] . Thrombolytic therapy seems to be most successful in distal clots, when used within 12 h after the onset of symptoms [66] .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…A less frequent indication for thrombolysis is mesenteric thromboembolism [22,23]. There are case reports in the literature showing good clinical results but no single large body of experience.…”
Section: Other Indicationsmentioning
confidence: 97%